Political communication of the Prime Minister of Malaysia Anwar Ibrahim on Twitter - Muhammad, Firdaus; Bakti, Andi M. Faisal; Johori, MD. Rozalafri; Saleh, Sadhriany Pertiwi (Otoritas : Jurnal Ilmu Pemerintahan, 2023)
Globalisation, information, and communication technology have changed human communication. The internet gave birth to social media and a new communication trend. Digital, such as computer-mediated, communication replaces traditional communication. Face-to-face communication can now be done via social media, which blurs space and time. The benefit is that social media is not controlled by mainstream media, which decides what to publish. Social media lets any communication actor broadcast messages to the public at any time. Some communication actors are government officials, or political actors. Anwar Ibrahim, the prime minister, wants to build political trust and support through vertical and horizontal political communication. Anwar Ibrahim regularly uses Twitter to engage with residents, show his actions, and express his attitude, commitment, and government vision. Politicians must adjust to social media's power. This study uses Nvivo 12 Pro for social media analysis. According to Nvivo, Anwar Ibrahim's political communication concentrated on his actions, government matters, political affairs, and maintaining his relationship with citizens and the king.